A Class of Solution of Orthogonal Plane MHD Flow through Porous Media in a Rotating Frame (Global Journal of Science Frontier Research, 2014)
Steady, two dimensional, incompressible electrically conducting, MHD fluid through porous media in a rotating reference frame under the presence of magnetic field which is mutually perpendicular to the velocity field has been considered. Complex variable technique has been employed and exact solutions for three different flow problems have been determined. Lastly, flows with isometric geometry have been studied.
Keywords: steady flow; stream function; complex variable technique; rotating reference frame; exact solution; MHD; porous media